THE INFLUENCE OF PRICE, PRODUCT QUALITY AND WORD OF MOUTH ON THE DECISION PURCHASE OF COFFEE PIE PRODUCTS AT TAKENGON CENTRAL ACEH - Rahma Yanti Br Damanik; Mariyudi; Adnan; Khairina AR (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
With diverse consumer lifestyles, including consumers in each region have their own unique cultural and culinary heritage. So prioritizing customer satisfaction is the ultimate goal for entrepreneurs, facing this situation every entrepreneur must adapt and recognize environmental conditions that are in accordance with current developments. This study aims to determine the effect of price, product quality and word of mouth on purchasing decisions for Takengon coffee pie products. The data in this study are primary data collected using a questionnaire method with a sample size of 105. The data in this study were analyzed using multiple linear regression methods. Research instrument tests, classical assumption tests and hypothesis tests were carried out with the SPSS 25.0 application tool. The results of the study showed that the price variable partially had a significant effect on purchasing decisions for Takengon coffee pie products. Furthermore, the price variable partially had a significant effect on purchasing decisions for Takengon coffee pie products. While the word of mouth variable did not have a significant effect on purchasing decisions for Takengon coffee pie products. Furthermore, simultaneously the price, product quality and word of mouth variables had a significant effect on purchasing decisions for Takengon coffee pie products. Therefore, it is important for business owners to provide prices and product quality that are in accordance with consumer expectations. In this way, consumers will feel satisfied, so they can provide positive reviews to decide to buy a product.